2011
DOI: 10.3113/fai.2011.0419
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Proximal Phalanx Size as a Guide for an Akin Closing Wedge Osteotomy

Abstract: We believe this method of the Akin osteotomy can improve the accuracy of the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…An Akin procedure 1 achieves angular correction of a hallux valgus deformity by means of a medial closing-wedge phalangeal osteotomy. 1,2,8,11,13,22,37,45,50,53 The primary indication for this procedure is an HVIP deformity. 8,11,13,50 The procedure can also be used in conjunction with almost any bunion correction in which some remaining valgus of the hallux is still present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An Akin procedure 1 achieves angular correction of a hallux valgus deformity by means of a medial closing-wedge phalangeal osteotomy. 1,2,8,11,13,22,37,45,50,53 The primary indication for this procedure is an HVIP deformity. 8,11,13,50 The procedure can also be used in conjunction with almost any bunion correction in which some remaining valgus of the hallux is still present.…”
Section: Discussionmentioning
confidence: 99%
“…No cases of delayed or nonunion were noted. Shannak et al 45 suggested that the Akin procedure can reliably achieve approximately 10 degrees of angular correction. The current prospective study reflects a similar experience, with no nonunions.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly evident in minimally invasive hallux valgus surgery, in which the Akin osteotomy is a vital part of the procedure to achieve greater corrections especially when performing the Chevron osteotomy for severe deformities. 17,18 Shannak et al 19 stated that an Akin osteotomy can be used to add 10° of correction after a first metatarsal osteotomy, but that corrections greater than 20° could lead to hallux varus and should not be performed. However, based on our findings, larger corrections are to be expected since 10% of those with abnormal HIAs had angles greater than 20°.…”
Section: Discussionmentioning
confidence: 99%
“…Frey et al 15 derived a trigonometric calculation to determine the amount of angular correction that can be expected from a certain size osteotomy wedge. Shannak et al 19 expanded upon this idea and used a similar calculation considering the different average widths of the proximal phalanx for males versus females, since the width of the proximal phalanx will change the size of the osteotomy base. Using their calculations as a reference, we can provide a guide as to how much bone to remove during an Akin osteotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation